2015
DOI: 10.1093/jnen/74.12.1158
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Soluble and Insoluble α-Synuclein to Mice

Abstract: The neurodegenerative synucleinopathies, which include Parkinson disease, multiple system atrophy, and Lewy body disease, are characterized by the presence of abundant neuronal inclusions called Lewy bodies and Lewy neurites. These disorders remain incurable and a greater understanding of the pathologic processes is needed for effective treatment strategies to be developed. Recent data suggest that pathogenic misfolding of the presynaptic protein, α-synuclein (α-syn), and subsequent aggregation and accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Studies investigating plaque initiation found Aβ plaques in animal brains intracranially injected with AD patient brain homogenates [1, 37]. Neurofibrillary tangles and Lewy Bodies were also seen in rodent brains injected with brains homogenates of tauopathy and synucleinopathy patients, respectively [10, 24]. The seeding of exogenous misfolded proteins initiated the aggregation of endogenous non-diseased protein, a characteristic similar to prion proteins involved in spongiform encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating plaque initiation found Aβ plaques in animal brains intracranially injected with AD patient brain homogenates [1, 37]. Neurofibrillary tangles and Lewy Bodies were also seen in rodent brains injected with brains homogenates of tauopathy and synucleinopathy patients, respectively [10, 24]. The seeding of exogenous misfolded proteins initiated the aggregation of endogenous non-diseased protein, a characteristic similar to prion proteins involved in spongiform encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Injection of recombinant preformed α-synuclein fibrils into specified brain regions in mice leads to intraneuronal aggregation of α-synuclein and propagation of the pathology, similar to what is observed in PD, indicating that an extracellular form of aggregated α-synuclein may be involved in this pathomechanism. [30][31][32][33][34][35] In preclinical studies, the murine homologue of PRX002 reduced intracellular α-synuclein pathology, protected neurons, and ameliorated cognitive and motor behavior deficits in multiple mouse models of α-synucleinopathy. 9,11,12,15,16 Targeting toxic proteins with monoclonal antibodies is also being evaluated as a potential therapeutic strategy in other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, with prion‐like spreading, it was possible to identify different strain conformations and seeding propensity, leading to distinct behavioral and histopathological phenotypes . Peripheral injections, intramuscular, intravenous, or intragastric, also induced cerebral α‐syn neuropathology in transgenic and wild‐type mice . These results indicate that inoculation of fibers, rather than oligomers, induces the propagation of LB/LN‐like inclusions throughout the brain.…”
Section: α Synuclein Oligomersmentioning
confidence: 93%